The molecular characterization of a catalase from Chinese mitten crab Eriocheir sinensis. (22nd November 2012) - Wang, M.; Wang, L.; Zhou, Z.; Gao, Y.; Wang, L.; Shi, X.; Gai, Y.; Mu, C.; Song, L.
Summary Catalase (CAT) is an antioxidant enzyme and plays a significant role in the protection against oxidative stress by reducing hydrogen peroxide. The CAT cDNA of Eriocheir sinensis (EsCAT) was cloned via RACE technique. The complete sequence of EsCAT cDNA consisted of a 5′ untranslated regions (UTR) of 224 bp, a 3′ UTR of 1287 bp with a poly (A) tail and an open reading frame (ORF) of 1542 bp, which encoded a polypeptide of 513 amino acid residues with a calculated molecular mass of approximately 58.86 kDa and a theoretical isoelectric point of 6.880. The deduced amino acid sequence of EsCAT contained a highly conserved proximal active‐site signature motif (60FDRERIPERVVHAKGAL76) and a proximal heme–ligand signature motif (350RLFSYNDTH358) and exhibited high similarity with other reported CATs. In the phylogenetic tree, EsCAT was clustered with the CATs from Scylla serrata and Portunus trituberculatus. The EsCAT transcripts were constitutively expressed in haepatopancreas, haemocytes, gill, gonad, muscle and heart, with highest expression level in haepatopancreas. The relative expression level of EsCAT mRNA in haemocytes was continuously up‐regulated and reached the peak level at 48 h post‐Vibrio anguillarum challenge. The purified recombinant EsCAT protein displayed antioxidant activity against hydrogen peroxide with high thermal stability and broad spectrum of pH values. All these results demonstrated that EsCAT was an efficient antioxidant enzyme and potentially involved in the regulation of redox and innate immune response of crabs.